Development of Moodle’s E-Learning as a Media in Mathematical Problem-Solving - Nurjannah, Nurjannah; Heriyanti, Anggy; Kaswar, Andi Baso (JTAM (Jurnal Teori dan Aplikasi Matematika), 2022)
The aim of this research is how to design an e-learning application that can be used as a medium in solving mathematical problems for Mathematics Education students at the Islamic Institute of Muhammadiyah Sinjai. The purpose of this research is to produce a product in the form of an e-learning application Moodle as a medium in solving problems. This study was designed using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. To get a valid and effective application, the validity of the research instrument was tested and the validity of the developed application was tested. Applications that have been implemented are then assessed by research subjects to determine their effectiveness. The research results obtained are: the application of e-learning Moodle as a medium in solving mathematical problems was declared to meet the validity and effectiveness. These results were obtained after being tested for validity by experts, which consisted of validating problem-solving instruments in the form of materials and problem-solving questions, all of which were in the valid category, namely 3.36, where the material aspect was 3.40 and the aspects of problem-solving questions problem is 3.33. Meanwhile, for application validation that is in the very valid category, the average validator value is 3.50. This application was effectively used based on student assessments of the efficiency of the application, display, and use of language which are in the very effective category with an average student assessment of 3.61 with a percentage of 90% so that this application was suitable for problem-solving for Mathematics Education students at the Islamic Institute of Muhammadiyah Sinjai.